2008
DOI: 10.1016/j.bmc.2008.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Design of antiangiogenic hypoxic cell radiosensitizers: 2-Nitroimidazoles containing a 2-aminomethylene-4-cyclopentene-1,3-dione moiety

Abstract: We designed chiral 2-nitroimidazole derivatives containing a 2-aminomethylene-4-cyclopentene-1,3-dione moiety as antiangiogenic hypoxic cell radiosensitizers. Based on results of molecular orbital calculations, the 2-aminomethylene-4-cyclopentene-1,3-dione moiety is expected to show high electrophilicity comparable to that of the 2-methylene-4-cyclopentene-1,3-dione moiety included in TX-1123 and tyrphostin AG17. We evaluated the antiangiogenic and radiosensitizing effects of the new compounds, along with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The metabolism and toxicology of nitroimidazole derivatives, particularly for secnidazole, have been characterized in recent reports [13,14]. Secnidazole (a, 2-dimethyl-5-nitro-1H-imidazole-1-ethanol) is extraordinarily effective in the treatment of giardiasis, amebiasis, and bacterial vaginosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism and toxicology of nitroimidazole derivatives, particularly for secnidazole, have been characterized in recent reports [13,14]. Secnidazole (a, 2-dimethyl-5-nitro-1H-imidazole-1-ethanol) is extraordinarily effective in the treatment of giardiasis, amebiasis, and bacterial vaginosis.…”
Section: Introductionmentioning
confidence: 99%
“…of -N-H), 3025 (ArC-H), 1690 (C=O stretching), 1225 cm -1 (C-O-C ether stretching); 1 H NMR (DMSO-d 6 ) d ppm: 227, 2.35, 2.45 (s, 9H, 3 9 CH 3 ), 5.96 (s, 2H, CH 2 ), 6.96-7.81 (m, 10H, Ar-H), 8.83 (s, 1H, CH=N), 11.22 (s, 1H, NH);13 C NMR (DMSO-d 6 ) (d): 14.28, 21.17, 21.49 (Ar-CH 3 ), 37.94 (CH 2 -CO), 107.16, 117.19, 122.23, 124.50, 128.44, 129.83, 130.47, 132.38, 136.92, 139.47, 143.47 (-CH=N), 149.22, 152.69, 153.58, 157.73 (Ar-C), 176.21 (C=O); Anal. Calcd.…”
mentioning
confidence: 99%
“…16) Indeed, using embryonated chicken eggs as an alternate model, it was reported that the in vivo activities of antiangiogenic and radiosensitizing agents could successfully be evaluated in eggs inoculated with tumor cells. [17][18][19] The in vivo antioxidative activity of redox nanoparticles was also previously assessed. 20) Based on these findings, we considered that the influence of ET on vascular permeability and leakage of intravenously injected agents from blood vessels could be evaluated using the embryonated chicken eggs having the vascular structure in the CAM.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the in vivo activity reflecting the pharmacokinetics of candidate compounds may be evaluable using this developing chicken egg model [11]. We have already succeeded in evaluating the in vivo activity of an antiangiogenic agent and a radiosensitizing agent by using this model [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%